'I also take part in caring for the sick child': a qualitative study on fathers' roles and responsibilities in seeking care for children in Southwest Ethiopia. Issue 8 (20th August 2020) - Funk, Tjede; Källander, Karin; Abebe, Ayalkibet; Alfvén, Tobias; Alvesson, Helle Mølsted
Abstract : Objectives: Fathers play an important role in household decision-making processes and child health development. Nevertheless, they are under-represented in child health research, especially in low-income settings. Little is known about what roles fathers play in the care-seeking processes or how they interact with the health system when their child is sick. This study aimed to understand Ethiopian fathers' roles and responsibilities in caring for their children when they are or become ill. Design: Qualitative study using semistructured interviews with fathers. Setting: This study was conducted in three rural districts of the Southern Nations, Nationalities and People's Region of Ethiopia. Participants: Twenty-four fathers who had at least one child between 2 and 59 months who visited a health extension worker with fever. Results: The overarching theme of this study was 'changing perceptions of paternal responsibilities during children's ill health'. It constituted three subthemes, namely, 'fathers' burden of earning money for care', 'fatherhood entails advocating children's healthcare needs' and 'investing in children's health can benefit the family in the future'. Fathers described that they were the ones mainly responsible for the financial arrangement of care and that this financial responsibility can involve stress when resources are scarce. Fathers knew what health services were available and accessible to them and were involved in different ways in the care seeking of the child. Changes in the importance ascribed to child health were expressed by fathers who described being more alert to children's ill-health. Conclusion: Fathers play various roles in the care-seeking process during children's illness episodes. This included, for instance, arranging resources to seek care, (co)-deciding where to seek care as well as accompanying the child to the health facility. The inability to organise necessary resources for care can lead to involuntary delays in care seeking for the child. This demonstrates the importance of including fathers in future interventions on maternal and child health.